Exploring game grammars: a sociosemiotic account of young people’s game-making practices - Paula, Bruno de (Visual Communication, 2021)
This article investigates the relationship between young people’s game-making practices and meaning-making in videogames. By exploring two different games produced in a game-making club in London through a multimodal sociosemiotic approach, the author discusses how semiotic resources and modes were recruited by participants to realize different discourses. By employing concepts such as modality truth claims and grammar, he examines how these games help us reflect on the links between intertextuality, hegemonic gaming forms and sign-making through digital games. He also outlines how a broader approach to what has been recently defined as the ‘procedural’ mode by Hawreliak in Multimodal Semiotics and Rhetoric in Videogames (2018) can be relevant for promoting different and more democratic forms of meaning-making through videogames.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Bridal Anxieties: Politics of Gender, Neoconservatism and Daytime TV in Turkey - Sayan-Cengiz, Feyda (Female Agencies and Subjectivities in Film and Television, 2020)
This chapter analyzes the reflections of Turkey’s neoconservative and neoliberal politics of gender on daytime television. The focus is on Bridal House, a popular daytime TV show in Turkey which interpellates women as domestic subjects competing with other women to prove their domestic abilities, particularly the ability to navigate the etiquette of domestic consumption. Hierarchies are instigated among women through symbolic battles on “tasteful” consumption, and the marital household surfaces as a space of constant regulation where women strive to be ideal housewives. By analyzing Bridal House through a Bourdieusian framework, this chapter traces the representations of the “ideal female subject” along neoconservative and neoliberal lines, and demonstrates the ways in which symbolic violences are enacted on women in contemporary Turkey’s daytime TV culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves - Çetin, Berfin Emre (Cambridge Scholars Publisher, 2015)
The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves explores the representation and reception of nationalism and masculinity in Turkey through an examination of the popular television serial, Valley of the Wolves which has been aired on Turkish television since 2003. This detailed examination of the show demonstrates a particular discourse of nationalism, namely the Turkish Islam synthesis embedded in a gender-specific regime in which the paramilitary hero is placed at the centre. The study draws on thirty-seven in-depth interviews with viewers of the programme from different social backgrounds. These viewers read the serial from various perspectives in the light of their gendered experiences, suggesting that the relationship between text and audience is not necessarily predetermined by the former, but is rather constructed through an interdiscursive process. The book also examines the pleasures of the “contesting” readers of Valley of the Wolves, drawing on the audience interviews, and argues that critical approaches to a particular media text do not present a barrier to audience pleasures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Consuming Halal Turkish Television in Indonesia: A Closer Look at the Social Responses Towards Muhteşem Yüzyıl - Rakhmani, Inaya; Zakiah, Adinda (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter unpacks the tension between secular, modern values and conservative, Islamic interpretations within the Indonesian middle class by taking the consumption of Turkish popular cultural products as a case. The chapter explicates the social responses towards the first Turkish television drama aired on terrestrial, private television in Indonesia: The Magnificent Century (Muhtesṃem Yüzyıl/Abad Kejayaan). This chapter understands the reproduction of secular and conservative Islamic values, while in contestation, as a response to broader global, market-capitalist developments. It finds that in response to audience criticism regarding the “un-Islamic” portrayal of the epoch in the drama—specifically the depiction of women as concubines—television stations enlisted the services of Muslim clerics to correct or justify the representation of historical facts. This reveals that market-driven self-censorship has opened up ways for Muslim clerics to influence television content. As such, the chapter argues that market-capitalist forces discursively use Islamic authority as a way to legitimise the halal consumption of Turkish drama among Indonesian Muslim audience at the expense of programme diversity.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Indonésie (corpus analysé); Indonésie (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

Mediatised Culturalisation Through Television: Second-Generation Alevi Kurds in London - Emre Cetin, Kumru Berfin (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Satellite television has not only provided migrant communities with stronger ties to their home countries but also enabled second-generation migrants in particular to know more about their country of origin beyond their family ties. The aim of this chapter is to explore the ways in which Turkish television contributes towards the making of the transnational identity of the “twice minority” group of Alevi Kurds through what I call mediatised culturalisation. Drawing on 17 in-depth interviews that I conducted with the second-generation members of the Alevi Kurdish community in London in 2016, I explore the role of Turkish television in contesting the boundaries of transnational social imaginaries of the second-generation viewers.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Royaume-Uni (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

Revisiting the Unplugged Margins: Rural Television Audiences and Mediatization - Türkoğlu, Nurçay (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter examines the social transformation of the television audience of rural Turkey. Villages near a metropolitan area, which were subject to an administrative decision to be relocated, were the focus of my fieldwork 30 years ago. Several visits between 1987 and 2019 to the same location, which is inhabited by television viewers and non-viewers alike, yielded an insightful mapping of engagement with popular culture via television at the periphery in Turkey from a historical perspective. While rural inhabitants are busy with daily labor in the countryside and are not keen on watching television, they are nonetheless aware of and connected to new, nationwide cultural trends and social changes. By reflexively discussing these experiences in ethnographic fieldwork on television habits and reception in rural Turkey over a 30-year span, I avoid the traps of modern-traditional and urban-rural binaries, allowing for an exploration of the role of television in mediating social change in the rural context and thus an analysis of the various complex layers and processes of mediatization among rural audiences.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

L’imbrication classe et sexe à l’œuvre : parcours identitaires et migratoires chez les personnes trans MtF latino-américaines - Gonzalez, Olga L. (Genre, Sexualité & Société, 2018)
Ce travail s’intéresse à la population trans MtF latino-américaine issue des secteurs populaires. Le travail a pour objectifs de (1) connaître les normes de genre du milieu d’origine de cette population (2) comprendre le lien du milieu d’origine avec leur parcours dans l’identité trans (3) examiner les parcours migratoires et comprendre leur très forte inscription dans la prostitution. L’enquête de terrain a été réalisée principalement en France et en Espagne. Concernant le cheminement identitaire, la recherche montre le poids de la formation sociale du milieu d’origine, et particulièrement le poids des normes relatives au genre dans les milieux populaires (hétéronormativité, homophobie, sanction des masculinités déviantes). Cette imbrication classe/sexe situe les personnes dans la position sociale marginale et stigmatisée de la prostitution. L’article apporte un éclairage sur cet environnement, où l’imaginaire festif côtoie l’ordinaire des violences. L’expérience migratoire, très valorisée dans le pays d’origine, est examinée. Le type de liens tissés avec la famille, et les difficultés liées à l’isolement linguistique et à la solitude sont abordés.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Orientalism - Said, Edward W (Penguin Books, 2019)
A groundbreaking critique of the West's historical, cultural, and political perceptions of the East that is—three decades after its first publication—one of the most important books written about our divided world. "Intellectual history on a high order ... and very exciting." —The New York Times In this wide-ranging, intellectually vigorous study, Said traces the origins of "orientalism" to the centuries-long period during which Europe dominated the Middle and Near East and, from its position of power, defined "the orient" simply as "other than" the occident. This entrenched view continues to dominate western ideas and, because it does not allow the East to represent itself, prevents true understanding. Source: Publisher
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

L'Atlantique noir: modernité et double conscience - Gilroy, Paul (Éditions Amsterdam, 2010)
Qu'est-ce que l'identité noire ? Contre ceux qui en défendent une conception ethniciste ou nationaliste, ou qui cherchent avant tout à en préserver l'authenticité, Paul Gilroy montre comment cette identité complexe, nourrie d'une diversité irréductible, repose sur l'existence d'un espace transnational en constante transformation, qui n'est pas spécifiquement africain, américain, caribéen ou britannique, mais tout cela à la fois : l'Atlantique noir. L'objet de ce livre est de donner à voir l''existence de cet espace constitué dès le XVIIe siècle à travers l'histoire de la traite négrière, de retracer ce réseau serré de relations, d'échanges à multiples sens, d'idées, d'hommes et de productions culturelles. Au fil de pages peuplées par les figures les plus hétéroclites, de Spike Lee à Walter Benjamin en passant par les Jubilee Singers, Richard Wright, W. E. B. Du Bois, Jimi Hendrix, Wynton Marsalis et Hegel, l'espace et le temps singuliers de l'Atlantique noir prennent forme et consistance de façon saisissante. La musique, mode d'expression de prédilection d'une culture enracinée dans l'expérience des terreurs indicibles de l'esclavage, avec ses usages et ses allers-retours inattendus d'un bord à l'autre de l'Atlantique, joue ici un rôle de premier plan. Le retour sur l'esclavage et son caractère intrinsèquement moderne, opéré dans les oeuvres de nombreux écrivains noirs, ouvre par ailleurs à une relecture critique de la modernité, d'une portée universelle, au même titre que la critique des conceptions figées et réductrices de l'identité.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Independent Videogames: Cultures, Networks, Techniques And Politics - Ruffino, Paolo (Routledge, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry – often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Queerness in Play - Harper, Todd; Adams, Meghan Blythe; Taylor, Nicholas (Palgrave Macmillan, 2018)
"Queerness in Play examines the many ways queerness of all kinds - from queer as 'LGBT' to other, less well-covered aspects of the queer spectrum - intersects with games and the social contexts of play. The current unprecedented visibility of queer creators and content comes at a high tide of resistance to the inclusion of those outside a long-imagined cisgender, heterosexual, white male norm. By critically engaging the ways games - as a culture, an industry, and a medium - help reproduce limiting binary formations of gender and sexuality, Queerness in Play contributes to the growing body of scholarship promoting more inclusive understandings of identity, sexuality, and games."--Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Gaming Cultures and Place in Asia-Pacific - Hjorth, Larissa; Chan, Dean (Routledge studies in new media and cyberculture, 2009)
This collection explores the relationship between digital gaming and its cultural context by focusing on the burgeoning Asia-Pacific region. Encompassing key locations for global gaming production and consumption such as Japan, China, and South Korea, as well as increasingly significant sites including Australia and Singapore, the region provides divergent examples of the role of gaming as a socio-cultural phenomenon. Drawing from micro ethnographic studies of specific games and gaming locales to macro political economy analyses of techno-nationalisms and trans-cultural flows, this collection provides an interdisciplinary model for thinking through the politics of gaming production, representation, and consumption in the region.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Black Europe Body Politics: Towards an Afropean Decolonial Aesthetics - Lockward, Alanna (Social Text Online, 2013)
The conceptualization of decolonial aesthetics is fairly recent, however its points of departure — the epistemic shifts that have been challenging coloniality in the artistic and cultural practices of the Global South — are as old as the colonial system. The defiance of colonialism in Vodou dance and rituals, which in Haiti ultimately led to the first successful enslaved people’s revolution, is a splendid case in point.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Decolonizing the Camera: Photography in Racial Time - Sealy, Mark Anthony (Durham University, 2015)
This thesis argues that photography is tainted with ingrained racist ideologies that have been present since its earliest inception in 1839. It considers the act of photographing the Other as a site of Western violence, myth, fantasy and disavowal. It examines archival images through the prism of race, representation and human rights with the aim of extracting new meanings that bring the Other into focus. This is done by reading the images both against the politics of the time in which they were made and as contemporary objects at work in the political and cultural present. The thesis makes the case that photography is burdened with ideological fault-lines concerning race and rights. The fault-lines have been forged by cultural and colonial violence resulting in Western scopic regimes that have dominated and fixed the Other within an inescapable set of Western epistemologies that have been used to serve and enhance imperial perspectives on race. I argue that these perspectives are still active within the Western mindset manifest as benign acts of photographic empathy that work to ultimately bolster Western hegemonies and economies. This thesis is based on 25 years of experience as a researcher and curator of international photography exhibitions, direct research into archives in different continental settings, the presentation of papers in a variety of national and international contexts, and interviews withphotographers, curators and academics. My hypothesis is that the history of photography can only be complete if the voice of the subaltern is made critically present within it, so allowing us to engage with important political racial memory work that can help us re-read the past and reconfigure different meanings concerning history, race, rights and human recognition in the present. I argue that photography requires decolonising work to be carried out on its history. I propose that if we do not recognise the historical and political conjunctures of racial politics at work within photography and the effects on those that have been culturally erased, made invisible or less than human by such images, then we remain hemmed within established orthodoxies of colonial thought concerning the racialised body, the subaltern and the politics of human recognition.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé